Serum value of Fasting C-peptide (FC-P), fasting insulin (FIns), and glycated hemoglobin (HbA1c) after Dynamic Blood Glucose Monitoring-guided Personalized Nutrition and Insulin Pump Therapy for Type II Diabetes Mellitus : Serum value of Fasting C-peptide (FC-P), fasting insulin (FIns), and glycated hemoglobin (HbA1c) - Zhu, Guohong (Journal of Medical Biochemistry, 2025)
Introduction: type 2 diabetes mellitus (T2DM) is a chronic metabolic disease requiring comprehensive management of multiple risk factors including blood glucose (BG), blood pressure, and lipids. It to investigate the clinical effects of individualized nutrition and insulin pump therapy guided by continuous glucose monitoring (CGM) based on the quality circle control (QCC) nursing model in T2DM patients and its effect on Fasting C-peptide (FC-P), fasting plasma glucose (FPG), 2-hour postprandial glucose (2 hPG), fasting insulin (FIns), and glycated hemoglobin (HbA1c).Materials and Methods: eighty T2DM patients treated at our hospital from January 2023 to January 2024 were recruited and rolled into a research group (EG) receiving individualized nutrition and insulin pump therapy guided by CGM based on the QCC nursing model, and a regular group (RG) receiving routine care and treatment. Differences of BG control, insulin usage, CGM downtime, and anomaly occurrence rate were compared between groups.Results: EG showed marked improvements relative to RG in mean fasting C-peptide (FC-P), fasting plasma glucose (FPG), postprandial 2-hour glucose (2 hPG), fasting insulin (FIns), and glycated hemoglobin (HbA1c) levels (P
Keywords: Serum value of Fasting C-peptide (FC-P), fasting insulin (FIns), and glycated hemoglobin (HbA1c) T2DM; continuous glucose monitoring; quality circle control nursing model; individualized nutrition; insulin pump therapy